2021
DOI: 10.3389/fonc.2021.638803
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Value of ARID5A and its Correlation With Tumor-Infiltrating Immune Cells in Glioma

Abstract: AT-rich interaction domain 5A (ARID5A) is a member of the ARID family with a function that has been linked to autoimmune as well as inflammatory diseases. Some ARID family members are involved in the initiation and progression of human cancers. However, the function of ARID5A in glioma remains unknown. In this study, ARID5A expression levels were analyzed using the Gene Expression Profiling Interactive Analysis (GEPIA) database. Subsequently, the relationship between ARID5A expression and the clinical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Different immunological states may influence the clinical course of the same type of tumor in different ways ( Zhou et al, 2021 ). In comparison to the high-CRLncSig group patients, the low-CRLncSig group patients had better stromal, immunological, and TME cells.…”
Section: Discussionmentioning
confidence: 99%
“…Different immunological states may influence the clinical course of the same type of tumor in different ways ( Zhou et al, 2021 ). In comparison to the high-CRLncSig group patients, the low-CRLncSig group patients had better stromal, immunological, and TME cells.…”
Section: Discussionmentioning
confidence: 99%
“…The research found that ARID5A regulates the inflammatory process, low expression of which is correlated with poor prognosis of lung cancer patients [ 43 ]. ARID5A is also a prognostic biomarker for glioma, which is correlated with immune infiltration [ 44 ]. ARID5B is associated with histone deacetylase-1, thereby affecting cell proliferation and differentiation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study determined the diagnostic and prognostic significance of Arid5a in gliomas and discovered a possible biological function for Arid5a ( 30 ). Low grade gliomas and GBM datasets were analyzed using online database, such as TCGA, and inversely correlated high expression of Arid5a with the prognosis of all stages of gliomas.…”
Section: Association Of Arid5a In Cancermentioning
confidence: 99%
“…Earlier studies reported that wild-type IDH lacks 1p/19q co-deletion and higher tumor grade was associated with poor prognosis in glioma ( 123 , 124 ). Another study reported high expression of Arid5a expression is associated with complex tumor malignancy ( 30 ), suggesting that Arid5a may be a useful marker for the degree of tumor malignancy.…”
Section: Association Of Arid5a In Cancermentioning
confidence: 99%
See 1 more Smart Citation